Násilí na pracovisti ve zdravotnictví : rámcov± návod pro resení [Framework guidelines for addressing workplace violence in the health sector] (Praha, 2004)
"The objective of these Framework Guidelines (from now on referred to as Guidelines) is to provide general guidance in addressing workplace violence in the health sector. Far from being in any way prescriptive, the Guidelines should be considered a basic reference tool for stimulating the autonomous development of similar instruments specifically targeted at and adapted to different cultures, situations and needs. The Guidelines cover the following key areas of action: - prevention of workplace violence - dealing with workplace violence - management and mitigation of the impact of workplace violence - care and support of workers affected by workplace violence - sustainability of initiatives undertaken."